Secure Attachment Priming Amplifies Approach Motivation for Infant Faces Among Childless Adults - Ding, Fangyuan; Jia, Yuncheng; Cheng, Gang; Wu, Lili; Hu, Tianqiang; Zhang, Dajun (Frontiers in Psychology, 2021)
Existing studies have indicated that priming secure attachment alters adults’ neural responses to infant faces. However, no study has examined whether this effect exists for motivational behavioral responses, and none of the previous studies included adult faces as a baseline to determine whether the security prime enhances responses to human faces in general or infant faces alone. To address this limitation, the current study recruited 160 unmarried and childless adults in the first phase, and all of them completed a battery of questionnaires, including the Interest in Infants, the Experiences in Close Relationships (ECR), and State Adult Attachment Measure (SAAM). A week later, after priming, 152 (76 security-primed vs. 76 neutrally primed) participants completed the SAAM and a behavioral program assessing their motivational responses to both adult and infant faces (i.e., liking, representational, and evoked responses). A manipulation check showed that the security prime was effective. Then, generalized linear mixed-effects models showed that security priming enhances adults’ liking, representational, and evoked responses (three components of the motivational system) only to infant faces and not to adult faces. Moreover, hierarchical regression analysis indicated that, even after security priming, there was a substantial linear relationship between positive motivation toward infant faces and the state of adult secure attachment. In summary, this study demonstrated for the first time that promoting the state of adult secure attachment can effectively enhance the effect size of the baby face schema. The current results were interpreted according to Bowlby’s view of the attachment behavioral system.